EKSPLORASI PENGGUNAAN CHATGPT SEBAGAI ASISTEN VIRTUAL DALAM PEMBELAJARAN FISIKA KUANTUM: ANALISIS KETERLIBATAN DAN PEMAHAMAN MAHASISWA - Romadon; Ahmad Fahrudin (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to explore the effectiveness of using ChatGPT as a virtual assistant in learning Quantum Physics at the university level. This study used a quasi-experimental design with a pretest-posttest control group approach, involving 60 students of the informatics engineering study program ITBA DCC Bandar Lampung, Indonesia, who were randomly divided into an experimental group (n=30) and a control group (n=30). The research instruments include concept comprehension tests, student engagement questionnaires, and observation sheets of learning activities. Data analysis was conducted using independent t-tests and quantitative descriptive analysis to assess differences in learning outcomes and levels of involvement between groups. The results showed that students in the experimental group using ChatGPT experienced a significant increase in understanding of Quantum Physics concepts (p < 0.05) compared to the control group, with higher cognitive, emotional, and behavioral engagement scores. These findings confirm that the integration of artificial intelligence technology, especially ChatGPT, is able to enrich Quantum Physics learning strategies through increased interactivity, learning independence, and the acquisition of complex concepts. The practical implications of this study support the adoption of pedagogically designed AI-based learning systems to optimize learning outcomes in higher education